The taxonomic status of Nectomys saturatus Thomas, 1897 (Cricetidae: Sigmodontinae) - Chiquito, Elisandra Almeida; Percequillo, Alexandre Reis (Zootaxa, 2019)
Nectomys (Sigmodontinae, Oryzomyini) is currently composed by five species: Nectomys apicalis, N. magdalenae, N. palmipes, N. rattus, and N. squamipes. These rodents have strong morphologic adaptations to semiaquatic habit and inhabit forests along river and streams in almost the entire South American continent. Although Nectomys is not a very speciose genus, 23 nominal taxa are associated with this group. Among these names is Nectomys saturatus, described in 1897 and currently allocated as synonym of N. apicalis, the west-Amazon species of Nectomys. Based on the examination of type material of the genus Nectomys, we hypothesize that Nectomys saturatus is a valid species. To test this hypothesis, we examined morphological and morphometric traits of 570 specimens of genus Nectomys of the same age class, belonging to the five recognized species, including the N. saturatus type series. We analyzed the external dimensions through descriptive statistics and we assessed the variation in craniodental measurements by means of Discriminant Analysis. Our results indicate N. saturatus individuals are considerably larger than the samples of congeneric species in all external traits, and they were also discriminated from the other species in the multivariate space. Qualitatively, N. saturatus shows two exclusive traits, the presence of paralophule on M1 and almost parallel-sided interorbital region. In this sense, our set of evidences indicates that our hypothesis should be accepted and the name Nectomys saturatus represents a valid species.